Estudo do papel do estresse oxidativo e dos antioxidantes na infecção por SARS-COV-2: uma revisão sistemática - Zatti, Pedro Henrique (My University, 2022)
With the arrival of SARS-CoV-2, the world found itself in a war against the disease caused by the virus. This one, which can lead to the compromise of systems, such as the cell cycle, stress, immunological and metabolic systems, leading to impairment of renin-angiotensin, which is involved in the functioning of vital organs. At the same time, there is an imbalance of the redox system, triggered by the storm of inflammatory cytokines, typical of the disease. These imbalances are important points for a worse prognosis of the disease, in addition to the existence of previous diseases and advanced age. For these reasons, much has been speculated about the use of antioxidants to prevent or fight viral. In this context, this systematic review sought to understand the effects of antioxidants on SARS-CoV-2 infection. Using the Medline/Pubmed database, data from retrospective and prospective clinical and observational studies were explored, selecting a total of 25 studies. The sample size ranged from 12 to 4314 individuals and the mean age was 55.27 ± 11.82. Most studies used vitamin D (n=6) as an intervention, followed by vitamin C (n=6) and zinc (n=3). As for the assessment of the quality of studies, an average score of 7.38 points for clinical studies and 9.28 points for observational studies was found, indicating good methodological quality. Although there is some evidence pointing to the benefits of using antioxidants against the disease, it is still not possible to reach a consensus on their real role, which is due to the heterogeneity of the studies and the discrepancy between the published results. [resumo fornecido pelo autor]
Com a chegada do SARS-CoV-2 o mundo se viu em uma guerra contra a doença causada pelo vírus. Essa, que pode acarretar o comprometimento de sistemas, com a do ciclo celular, do estresse, imunológicos e metabólicos, levando ao comprometimento da renina-angiotensina, que está envolvida no funcionamento de órgãos vitais. Paralelamente, se tem um desequilíbrio do sistema redox, desencadeado pela tempestade de citocinas inflamatórias, típica da doença. Esses desequilíbrios são pontos importantes para um pior prognóstico da doença, além da existência de doenças prévias e a idade avançada. Por essas razões, muito se especulou sobre o uso de antioxidantes para prevenção ou combate viral. Neste contexto, a presente revisão sistemática buscou compreender os efeitos dos antioxidantes diante da infecção por SARS-CoV-2. Usando a base de dados Medline/Pubmed, foram explorados dados de estudos clínicos e observacionais retrospectivos e prospectivos, selecionado um total de 25 estudos. O tamanho amostral variou de 12 a 4314 indivíduos e a idade média foi de 55,27 ± 11,82. A maioria dos estudos utilizou a vitamina D (n=6) como intervenção, seguido pela vitamina C (n=6) e zinco (n=3). Quanto a avaliação da qualidade dos estudos, foi encontrado um escore médio de 7,38 pontos para estudos clínicos e 9,28 pontos para estudos observacionais, indicando boa qualidade metodológica. Apesar de haver algumas evidências que apontam para os benefícios do uso de antioxidantes frente à doença, ainda não é possível se ter um consenso sobre seu real papel, motivo dado pela heterogeneidade dos estudos e a discrepância entre os resultados publicados. [resumo fornecido pelo autor]
Keywords: COVID-19; Estresse oxidativo; Inflamação; Micronutrientes; Fenóis